AGE ASPECTS OF THE FORMATION AND DYNAMICS OF DEVELOPMENT OF EXCESS BODY WEIGHT AND HYPERGLYCEMIA IN PREGNANT WOMEN (PROSPECTIVE EPIDEMIOMONITORING) - Mamasaliev N. S.; Kuzieva G. A.; Asrankulova D. B.; Mirsaydullaev M. M.; Usmonov B. U. (Modern American Journals, 2025)
Аrterial hypertension (AH) in pregnant women occupies a special place among the pressing issues of modern medicine. It is an integral part of at least two extremely acute medical and social problems today: hypertension in general and the reproductive health of the nation. The main problem of hypertension in pregnant women: the lack of a unified terminology, the use of different classification and criteria for hypertension, tactics of patient management. We tried, on the basis of evidence-based medicine, to present the classification of hypertension in pregnant women and the principles of drug therapy, including emergency care in hypertensive crisis.
Keywords: Epidemiology, pregnancy, arterial hypertension, hypertensive and vegetative crises, pharmacotherapy.